SOCIAL CONCERN FOR MUSIC: संगीत का सामाजिक सरोकार - Singh Tomar, Awadhesh Pratap (International Journal of Research -GRANTHAALAYAH, 2015)
The result of a person's creative image and creativity is the rise of fine arts. Theatrical, music and visual materials (paintings and crafts) created for the purpose of publicity and time sharing are also serving other purposes. Public awakening and the spread of social consciousness is an act that has been edited since the middle of music since ancient times and continues even today. Many social objectives and goals were propagated through the singing of Vedic hymns such as praising the rivers and drawing attention to their conservation and relevance, they were considered to be revered as Annadri. व्यक्ति की रचनात्मक प्रतिमा एवं सृजनशीलता का परिणाम ललित कलाआंे का उदय है। जनचित्तरंजन एवं समय बांटने के उद्वेश्य से रची गयी नाट्य, संगीत एवं दृष्य सामग्रियां (चित्र एवं शिल्प) आज अन्य उद्देश्यों की पूर्ति भी कर रही है। जन जागरण और सामाजिक चेतना का प्रसार एक ऐसा कार्य है जो संगीत के मध्य से प्राचीन काल से संपादित होता आया है और आज भी जारी है। वैदिक ऋचाओं के गायन के माध्यम से अनेक सामाजिक उद्देश्यों एवं लक्ष्यों को प्रसारित किया गया जैसे नदियांे की प्रशंसा करके उनके संरक्षण एवं सुचिता पर ध्यान आकर्षित कराया गया उन्हंे अन्न दात्री मानकर पूजनीय माना गया।